Self-repairing thermal insulation material for medium-high pressure steam pipeline and preparation method of self-repairing thermal insulation material

By designing the use of self-repair composite powder and modified waste aluminum silicate refractory fibers, combined with lightweight drift beads and other materials, the problem of insufficient insulation performance and automatic repair of medium and high pressure steam pipeline insulation materials is solved, and high isolation is achieved Self-healing insulation material with thermal properties and long life.

CN119191811APending Publication Date: 2024-12-27武汉钢铁有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411370326.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing medium and high-pressure steam pipelines have single types of insulation materials, insufficient thermal insulation performance, and have problems such as deterioration of structural and material properties, falling off and breaking, and large heat loss during long-term use, and automatic repairs have not been achieved.

Method used

Using self-healing composite powder and modified waste aluminum silicate refractory fiber, it is modified through ultrasonic vibration screening and polyethylene glycol solution surface, combined with light drift beads, gas-phase nanosilicon dioxide, titanium dioxide and potassium hexattitanate Whiskers, a composite particle material designed with core-shell structure, realizes automatic repair of materials and high thermal insulation performance.

Benefits of technology

It has achieved good thermal insulation structure in medium and high pressure steam pipelines, high thermal barrier and heat reflection performance, self-repairing and self-repairing insulation materials, green and environmentally friendly and waterproof, extending service life and reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067410930000111
    Figure BDA0005067410930000111
  • Figure BDA0005067410930000121
    Figure BDA0005067410930000121
  • Figure HDA0005067410960000011
    Figure HDA0005067410960000011
Patent Text Reader

Abstract

The invention discloses a self-repairing thermal insulation material for medium and high pressure steam pipelines. The self-repairing thermal insulation material comprises the following raw materials in percentage by weight: 10-15% of self-repairing composite powder, 3-5% of fumed nano-silica, 2-3% of titanium dioxide, 2-3% of potassium hexatitanate whiskers, 20-32% of modified waste aluminum silicate refractory short fibers, 8-12% of light floating beads, 6-9% of a coagulant, 23-33% of a binder, 1.5-3.5% of a composite water reducer and 0.1-0.2% of a retarder, the self-repairing composite powder is prepared from the following raw materials: self-crosslinking acrylate emulsion, ammonium polyphosphate, dipentaerythritol, melamine, silicon-aluminum oxide heat-insulating filler powder and water. The thermal insulation material disclosed by the invention has the advantages of good thermal insulation structure integrity, high thermal barrier and thermal reflection performance, good crack self-repairing performance, good waterproofness and the like, and is suitable for the fields of medium-high pressure steam pipelines and the like; the resource utilization of the waste refractory fibers can be realized, and good economic and environmental benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal insulation materials, and in particular relates to a self-repairing thermal insulation material for medium and high pressure steam pipelines and a preparation method thereof. Background Art

[0002] Steam is the most common energy medium used in daily production at steel and petrochemical plants. As a transportation channel, steam pipes require excellent thermal insulation. This is especially true for medium- and high-pressure steam pipelines, where high pressures and temperatures (380-545°C, 2.50-8.83 MPa) directly impact the efficiency and output of power generation units. Therefore, pipeline thermal insulation is crucial. However, currently, there are no insulation materials specifically designed for medium- and high-pressure steam pipelines.

[0003] The existing technology still mainly uses a multi-layer thickened structure of aluminum silicate needle-punched blankets, and a small number of them use aerogel insulation felts for thermal insulation reinforcement. For example, patent CN114738548A discloses a high-pressure steam pipeline insulation structure and construction method. The outer insulation layer uses a multi-layer structure of aerogel insulation felt, a first aluminum foil fiberglass cloth, a first aluminum silicate insulation blanket, a second aluminum foil fiberglass cloth, and a second aluminum silicate insulation blanket. The thermal insulation performance of the steam pipeline insulation layer is improved to meet the higher thermal insulation requirements of high-pressure steam pipelines. However, the multi-layer wrapping method leads to many construction steps, difficult splicing parts, and large actual interlayer thermal resistance. It also cannot avoid problems such as poor waterproof performance and loosening and sinking during long-term service cycles. In addition, existing patents and literature reports have not yet proposed a solution to the problem of automatic repair of cracks and damage in steam pipeline insulation materials during their service cycle. Summary of the Invention

[0004] The main purpose of the present invention is to provide a self-repairing thermal insulation material for medium and high-pressure steam pipelines and a preparation method thereof, so as to solve the problems existing in the thermal insulation protection of existing medium and high-pressure steam pipelines (steam temperature 380-545°C, 2.50-8.83MPa), such as the single type of thermal insulation materials, insufficient thermal insulation performance, and structural and material performance degradation, shedding and damage, and large heat loss during long-term use. The present invention has the advantages of good thermal insulation structure integrity, high thermal barrier and heat reflection performance, self-repair of cracks, green environmental protection and good waterproofness.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A self-repairing thermal insulation material for medium- and high-pressure steam pipelines comprises the following raw materials in percentage by weight: 10-15% self-repairing composite powder, 3-5% fumed nano-silica, 2-3% titanium dioxide, 2-3% potassium hexatitanate whiskers, 20-32% modified waste aluminum silicate refractory short fibers, 8-12% lightweight floating beads, 6-9% coagulant, 23-33% binder, 1.5-3.5% composite water reducer, and 0.1-0.2% retarder; the modified waste aluminum silicate refractory fibers are obtained by vibrating and screening waste aluminum silicate refractory fibers and surface-modifying them using a polyethylene glycol solution, and include two sizes of 1-1.5 mm and 3-5 mm; the raw materials of the self-repairing composite powder comprise self-crosslinking acrylic emulsion, high polyammonium phosphate, dipentaerythritol, melamine, silicon aluminum oxide thermal insulation filler powder, and water.

[0007] In the above scheme, in the self-repairing insulation material for medium and high pressure steam pipes, the content of 3-5 mm modified waste aluminum silicate refractory short fibers is 8-15%, and the content of 1-1.5 mm modified waste aluminum silicate refractory short fibers is 15-28%.

[0008] Furthermore, the waste aluminum silicate refractory fibers are waste aluminum silicate refractory fibers that do not contain zirconium or waste aluminum silicate refractory fibers that contain zirconium.

[0009] Furthermore, the zirconium-free waste aluminum silicate refractory fibers are taken from industrial waste whose working environment is an oxidizing atmosphere with a medium- and long-term working temperature lower than 900°C, or a reducing atmosphere with a medium- and long-term working temperature lower than 700°C; the zirconium-containing waste aluminum silicate refractory fibers are taken from industrial waste whose working environment is an oxidizing atmosphere with a medium- and long-term working temperature lower than 1100°C, or a reducing atmosphere with a medium- and long-term working temperature lower than 900°C.

[0010] Furthermore, the vibration screening step includes: shearing the waste aluminum silicate refractory fibers into short fibers of 3 to 5 mm, and then screening them using a vibration screen with an aperture of 3 mm to remove the deteriorated refractory fibers that have become brittle and powdered due to high-temperature crystallization, and taking the part above the sieve to obtain 3 to 5 mm waste aluminum silicate refractory short fibers; then taking part of the waste aluminum silicate refractory short fibers and continuing to shear them into short fibers of 1 to 1.5 mm, and screening them using a vibration screen with an aperture of 1 mm to obtain 1 to 1.5 mm waste aluminum silicate refractory short fibers.

[0011] Furthermore, the vibrating screen is an ultrasonic vibrating screen. When the vibrating screen motor is turned on, the ultrasonic waves generated by the ultrasonic generator are coupled (ultrasonic power 0.55-1.1kW, vibration frequency 20-30kHz, amplitude 15-20um, vibration time 3-5min) to break and screen out the deteriorated refractory fibers that have become brittle and powdered due to high-temperature crystallization.

[0012] Furthermore, the concentration of the polyethylene glycol solution is 0.7-0.8 g / 100 mL.

[0013] Furthermore, the surface modification step includes: sending the waste aluminum silicate refractory short fibers into a closed spray operation chamber through a conveyor belt, a rotary sprayer is provided on the top of the spray operation chamber to spray the polyethylene glycol solution, and a nozzle is provided at the bottom of the conveyor belt. The waste aluminum silicate refractory fibers are blown into the air by spraying compressed air to fully contact with the polyethylene glycol spray. After the spraying is completed, they are sent out of the spray operation chamber through a conveyor belt and left to stand (15 to 20 minutes).

[0014] Furthermore, for a unit amount of waste aluminum silicate refractory fibers (1 kg), the spraying amount of the polyethylene glycol solution is 100 to 150 mL.

[0015] Furthermore, in the self-repairing composite powder, the raw materials and their mass percentages include: 20-35% self-crosslinking acrylic emulsion, 10-15% high polyammonium phosphate, 3-6% dipentaerythritol, 4-8% melamine, 20-35% silicon aluminum oxide insulation filler powder, and 18-28% water.

[0016] In the above scheme, the self-repairing composite powder is obtained by stirring self-crosslinking acrylic emulsion, high polyammonium phosphate, dipentaerythritol, melamine, silicon aluminum oxide insulation filler powder and water in proportion (10 to 20 minutes), drying (110 to 130° C.), breaking up and grinding.

[0017] In the above solution, the particle size of the self-repairing composite powder is less than 1200 mesh.

[0018] In the above scheme, the self-crosslinking acrylate emulsion is anionic, the main synthetic monomers are acrylate and methacrylate, the solid content is ≥40%, the average particle diameter is 0.2-0.4 μm, and the pH value is 6.0-8.0.

[0019] Furthermore, the polymerization degree of the high polyammonium phosphate is ≥1000.

[0020] In the above solution, the particle size of the silicon aluminum oxide thermal insulation filler powder is less than 1600 mesh.

[0021] Furthermore, the silicon aluminum oxide thermal insulation filler powder is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers.

[0022] Furthermore, the high-energy ball milling treatment uses a planetary high-energy ball mill with a rotation speed of 450-550 rpm, a ball milling time of 3-6 hours, a medium filling rate of 0.3-0.45, and a ball-to-material ratio of (3-5):1.

[0023] Furthermore, the high-energy ball milling treatment introduces a grinding aid, the amount of which is 3-6% of the mass percentage of the 1-1.5 mm waste aluminum silicate refractory short fibers; specifically, anhydrous ethanol can be selected.

[0024] Preferably, the particle size of the light floating beads is 80-200 mesh, and the bulk density is ≤0.43g / cm 3 .

[0025] Preferably, the density of the fumed nano-silica is ≤0.05 g / cm 3 , specific surface area ≥600m 2 / g, particle size is 7-40nm, SiO2 content ≥99.8%.

[0026] Preferably, the titanium dioxide is rutile, has a particle size of ≤300 mesh, and a TiO2 content of ≥94wt%.

[0027] Preferably, the potassium hexatitanate whiskers have a diameter of 2-4 μm and an aspect ratio of 10-20.

[0028] Preferably, the coagulant is sintered magnesia powder with a MgO content of ≥98wt% and a particle size of 300 mesh or less.

[0029] In the above solution, the binder includes silica sol and water-based silicone resin.

[0030] Furthermore, the silica sol has a SiO2 content of 30-40% and a pH value of 9.0-9.5; the water-based organic silicone resin is an ionic water-based organic silicone resin with a temperature resistance of ≥600°C, a solid content of ≥45%, and a pH value of 6.0-8.0.

[0031] Furthermore, the mass ratio of the silica sol to the water-based silicone resin is (2-5):1.

[0032] In the above solution, the composite water reducer includes polycarboxylic acid high-efficiency water reducer and sodium tripolyphosphate.

[0033] Furthermore, the water reduction rate of the polycarboxylic acid high-efficiency water reducer is 30-40%.

[0034] Furthermore, the mass ratio of the polycarboxylate high-efficiency water reducer to sodium tripolyphosphate is 1:(3.2-10.5).

[0035] Preferably, the retarder is citric acid.

[0036] The present invention also provides a method for preparing a self-repairing thermal insulation material for medium and high pressure steam pipelines, comprising the following steps:

[0037] 1) Weigh the modified waste aluminum silicate refractory short fibers, self-repairing composite powder, lightweight floating beads, fumed nano-silica, titanium dioxide, potassium hexatitanate whiskers, coagulant, composite water reducer and retarder according to the ratio, first add part of the modified waste aluminum silicate refractory short fibers and the entire amount of lightweight floating beads into the blender, stir (3 to 5 minutes), then add the weighed self-repairing composite powder, fumed nano-silica, titanium dioxide, potassium hexatitanate whiskers, coagulant and retarder, add the remaining amount of modified waste aluminum silicate refractory short fibers under stirring conditions, stir (5 to 10 minutes) to obtain a solid mixture;

[0038] 2) The solid mixture and the binder are mixed and stirred evenly (5 to 10 minutes) to obtain the self-repairing thermal insulation material for medium and high pressure steam pipelines.

[0039] In the above scheme, in step 1), the modified waste aluminum silicate refractory short fibers include modified waste aluminum silicate refractory short fibers with lengths of 3 to 5 mm and 1 to 1.5 mm, respectively. During the feeding process, 2 / 3 of the modified waste aluminum silicate refractory short fibers with a length of 3 to 5 mm and the entire amount of the modified waste aluminum silicate refractory short fibers with a length of 1 to 1.5 mm are added first; and then (after adding raw materials such as self-repairing composite powder, coagulant and retarder) the remaining amount of modified waste aluminum silicate refractory short fibers with a length of 3 to 5 mm is added.

[0040] The self-repairing insulation material for medium and high pressure steam pipelines prepared according to the above scheme needs to be sprayed within 30 minutes; it is suitable for thermal insulation protection of medium and high pressure steam pipelines with steam temperatures of 380 to 545°C.

[0041] The principle of the present invention is:

[0042] Through the design of self-healing materials, silicon aluminum oxide made from used refractory fibers is used as the thermal insulation filler, a combination of high polyammonium phosphate, dipentaerythritol, and melamine is used as the foaming agent, and a self-crosslinking acrylic emulsion is used as the bonding agent. Through self-crosslinking polymerization, the thermal insulation filler and foaming agent are encapsulated. At the same time, melamine also acts as a crosslinking agent, providing a large number of free radicals, which synergistically promote the interfacial bonding between the self-crosslinking acrylic emulsion and the powder particles, forming a core-shell structured composite particle self-healing material, which improves the material's stability and waterproofness. The formula is designed to make it begin to decompose and foam at temperatures above 350°C. When the medium and high pressure steam pipeline is operating normally (steam temperature 380-545°C), the temperature of the adjacent area in contact with the steam pipeline increases (≥350°C). The volume expansion caused by the thermal foaming forms a porous thermal insulation material with a low thermal conductivity coefficient, which can fill the gaps between the refractory fibers and further improve the thermal insulation performance. In addition, as the service time continues to increase, the insulation material itself will inevitably shrink and crack, and its structure and performance will deteriorate. When cracks appear inside and heat is conducted outward through the gaps, the thermal insulation performance of the insulation layer decreases and the temperature around the cracks rises. When the temperature exceeds 350°C, the self-healing material around the cracks expands due to the heat, forming a porous insulation material to fill and compensate for the cracks, thereby realizing automatic repair of the material during service, thereby improving the overall thermal insulation performance and extending the service life.

[0043] By using the zirconium-free aluminum silicate refractory fibers or zirconium-containing aluminum silicate refractory fibers discarded from metallurgical furnaces as the main raw materials, waste refractory short fibers and silicon aluminum oxide thermal insulation filler powder are prepared. The raw materials are cheap, easy to obtain and high in purity. The good thermal insulation ability of the refractory fibers is utilized to improve the thermal insulation performance and tensile strength of the spray coating, while reducing carbon dioxide emissions and environmental pollution. In order to solve the technical problems of performance degradation caused by crystallization, pulverization, hardening and easy breakage of waste refractory fibers, the improvement measures adopted are as follows: First, screening is carried out from the source of raw materials, by selecting non-zirconium-aluminum silicate refractory fibers or zirconium-aluminum silicate refractory fibers used in the thermal insulation layer of metallurgical furnaces, and the non-zirconium-aluminum silicate refractory fibers have a long-term working temperature lower than 900°C in an oxidizing atmosphere or a long-term working temperature lower than 700°C in a reducing atmosphere; the zirconium-aluminum silicate refractory fibers have a long-term working temperature lower than 1100°C in an oxidizing atmosphere or a long-term working temperature lower than 900°C in a reducing atmosphere, which is lower than the non-zirconium-aluminum silicate refractory fibers (950°C in an oxidizing atmosphere, 750°C in a reducing atmosphere). ) and zirconium-containing aluminum silicate refractory fibers (1150°C in oxidizing atmosphere and 950°C in reducing atmosphere), which greatly reduces the proportion of crystallization in waste refractory fibers; secondly, the waste aluminum silicate refractory fibers are sheared and screened using an ultrasonic vibrating screen. When the vibrating screen motor is turned on, the ultrasonic wave generated by the ultrasonic generator is coupled to utilize the characteristics of the crystallized fibers that are relatively dense and fragile relative to the amorphous fibers. The deteriorated crystallized refractory fibers that have become brittle and powdered due to high-temperature crystallization are broken and screened out. At the same time, the deteriorated slag balls and crystallization particles attached to the surface of normal refractory fibers that are difficult to screen out with conventional mechanical vibrating screens can be removed through ultrasonic vibration, thereby further improving the thermal insulation performance and stability of the recycled waste aluminum silicate refractory fibers. Finally, in order to enhance the toughness of aluminum silicate refractory fibers, improve the interfacial bonding of refractory fibers and their dispersion in the spray coating, the surface of the waste refractory fibers was modified with a polyethylene glycol aqueous solution at a concentration of 0.7-0.8 g / 100 mL, and the efficiency and uniformity of the modification operation were improved by spraying in the upper part of the spray operation chamber and blowing in the lower part.

[0044] To achieve excellent thermal insulation, in addition to utilizing either zirconium-free or zirconium-containing aluminum silicate refractory fibers with excellent thermal insulation properties, an optimized combination of lightweight bubbling beads, fumed nano-silica, rutile titanium dioxide, and potassium hexatitanate whiskers is employed to further reduce thermal conductivity and increase infrared reflectivity, thereby enhancing the thermal insulation capability of the pipeline insulation layer and reducing heat loss. The addition of lightweight bubbling beads leverages their typical hollow spherical closed pore structure to increase the number of micron-sized closed pores, further reducing thermal conductivity. The spherical particles' excellent fluidity improves the material's sprayability. Fumed nano-silica, evenly dispersed within the gaps between the refractory fibers and lightweight bubbling beads, leverages its nanoscale pore size and ultra-low thermal conductivity to further reduce the material's thermal conductivity and enhance thermal insulation. The addition of rutile titanium dioxide, leveraging its excellent chemical stability, dispersibility, and high infrared reflectivity, further enhances the material's thermal insulation performance by reflecting mid- and long-wave infrared radiation below 500°C. By adding potassium hexatitanate whiskers, taking advantage of their excellent mechanical properties, low thermal conductivity, negative temperature coefficient and high infrared reflection characteristics, the conductivity of the spray coating is reduced from three aspects: structural insulation, physical insulation and infrared reflection. At the same time, the strengthening and toughening effects of the reinforced fibers are further supplemented to make up for the shortcomings of insufficient toughness and strength of the refractory fibers after use.

[0045] By adding sintered magnesia sand coagulant with a particle size of less than or equal to 300 mesh, and utilizing the physical and chemical effects between magnesium oxide, silica sol and water-based silicone resin, the reaction of anions on the surface of the sol is promoted, the formation and gelation rate of the siloxane group is accelerated, and the coagulation and bonding of the binder are accelerated, rapid hardening can be achieved, and the curing time can be significantly shortened (to 2 hours), thereby shortening the construction period.

[0046] By using silica sol and water-based silicone resin as composite binders, the pH value can be adjusted to effectively control the curing time of the material to meet construction requirements. At the same time, the silica sol is hydrated and gelled and crystallized inside the material. The large number of micropores generated during molding can further improve the thermal insulation performance. In addition, the water-based silicone resin is coated on the surface of the refractory fiber and powder, and its hydrophobicity is utilized to improve the waterproof performance of the spray coating insulation layer, reduce the impact of rainwater leakage on the insulation layer during the use of the steam pipeline, and increase the service life. The present invention uses a composite binder based on silica sol and water-based silicone resin, which can effectively ensure the mechanical properties and bonding properties of the coating system while controlling costs.

[0047] By adding citric acid retarder, citric acid is reacted with MgO particles in sintered magnesia to form a low-solubility magnesium citrate protective layer, which can control the hydration rate of magnesium oxide, thereby reducing the viscosity of the binder, improving the fluidity of the spray coating, promoting the coagulation and hardening of the matrix, and improving the strength.

[0048] Through the optimized combination of polycarboxylic acid high-efficiency water reducer and sodium tripolyphosphate, the performance shortcomings of a single water reducer are avoided, the construction fluidity of the spray coating is improved, and the amount of binder is reduced, achieving the effect of high water reduction rate without segregation.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] 1) The present invention provides a self-repairing thermal insulation material for medium- and high-pressure steam pipelines, which is suitable for thermal insulation protection of medium- and high-pressure (2.50-8.83 MPa) steam pipelines with steam temperatures of 380-545°C. The resulting thermal insulation material has the advantages of good insulation structure integrity, high heat barrier and heat reflection properties, self-repair of cracks, environmental friendliness, and good waterproofness.

[0051] 2) The design of low-thermal-conductivity self-healing materials improves the thermal insulation performance of areas close to the hot surface of the pipeline. At the same time, when cracks appear during service, causing the temperature of areas away from the hot surface of the pipeline to rise and cause the thermal protection to fail, the porous thermal insulation material is formed by self-expansion to fill and repair the cracks, achieving automatic repair of the thermal insulation material. This solves the problems of structural and material performance degradation, shedding and damage, and large heat loss that exist in existing steam pipeline insulation materials during long-term use. At the same time, the thermal insulation performance of the material is significantly improved by combining modified refractory fibers, lightweight floating beads, fumed nano-silica, potassium hexatitanate whiskers and other materials;

[0052] 3) The present invention utilizes water-based silicone resin to coat the surface of refractory fibers and powders, and utilizes its hydrophobicity to modify the surface of the materials, thereby improving the waterproof performance of the thermal insulation materials; at the same time, the design of core-shell structured composite particles in the self-healing material is utilized to improve the stability and waterproofness of the materials.

[0053] 4) The present invention uses waste aluminum silicate refractory fibers after use as the main raw material, which can effectively reduce the preparation cost, has good economic and environmental benefits, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a scanning electron microscope image of a sample of the self-repairing thermal insulation material for medium- and high-pressure steam pipelines obtained in Example 1 after heat treatment at 400°C for 3 hours;

[0055] Figure 2 This is the XRD diffraction pattern of the sample of the self-repairing thermal insulation material for medium and high pressure steam pipelines obtained in Example 1 after heat treatment at 400°C for 3 hours. DETAILED DESCRIPTION

[0056] The following examples and comparative examples clearly and specifically describe the technical solutions adopted in the present invention. The examples and comparative examples are merely examples to illustrate the present invention, do not represent all embodiments, and do not limit the scope of the present invention. The embodiments of the present invention, as well as various changes or modifications made by those skilled in the art based on the present invention, are equivalent to those described in the present invention.

[0057] In the following examples, the zirconium-free waste aluminum silicate refractory fibers are taken from zirconium-free waste aluminum silicate refractory fiber blankets / modules for insulation of silicon steel bell furnace linings (reducing H2 atmosphere, medium- and long-term operating temperature 550-700°C).

[0058] The zirconium-containing waste aluminum silicate refractory fiber used is taken from the zirconium-containing waste aluminum silicate refractory fiber module for the lining of the soaking section of the CSP soaking furnace (oxidizing atmosphere, medium and long-term operating temperature 1000-1100°C).

[0059] The preparation method of the modified waste aluminum silicate refractory fiber comprises the following steps: 1) cutting the recovered waste aluminum silicate refractory fibers into short fibers of 3 to 5 mm, and then screening them with an ultrasonic vibrating screen with an aperture of 3 mm (vibration frequency of 20 to 30 kHz, amplitude of 15 to 20 μm, and vibration time of 3 to 5 min). When the vibrating screen motor is turned on, the ultrasonic wave generated by the ultrasonic generator is coupled to break and screen out the deteriorated refractory fibers that have become brittle and powdered due to high-temperature crystallization, thereby obtaining 3 to 5 mm waste aluminum silicate refractory short fibers; 2) then taking part of the waste aluminum silicate refractory short fibers and continuing to cut them into short fibers of about 1 to 1.5 mm, and screening them with an ultrasonic vibrating screen with an aperture of 1 mm. The deteriorated slag balls and crystallization particles attached to the surface of the normal refractory fibers that are difficult to be screened out by conventional mechanical vibrating screens are removed by ultrasonic vibration, thereby obtaining 1 to 1.5 mm waste aluminum silicate refractory fibers. short fibers; 3) finally, the obtained 3-5 mm waste aluminum silicate refractory short fibers and 1-1.5 mm waste aluminum silicate refractory short fibers are respectively sent into a closed spray operation chamber through a conveyor belt, and a rotary sprayer is provided on the top of the spray operation chamber to spray polyethylene glycol PEG-4000 aqueous solution (wherein the concentration adopted in Examples 1, 2, and 5 is 0.7 g / 100 mL, and the spraying amount is 150 mL / Kg; the concentration adopted in Examples 3 and 4 is 0.8 g / 100 mL; the spraying amount is 100 mL / Kg), and a nozzle is provided at the lower part of the conveyor belt, and the waste aluminum silicate refractory short fibers are blown into the air by spraying compressed air to fully contact with the polyethylene glycol spray. After the spraying is completed, they are sent out of the spray operation chamber through a conveyor belt and allowed to stand (15-20 min) to obtain 3-5 mm modified aluminum silicate refractory short fibers and 1-1.5 mm modified aluminum silicate refractory short fibers, respectively.

[0060] In the following examples, the silica sol is provided by Guangdong Huierte Nano Technology Co., Ltd., and its SiO2 content is 40% and the pH value is 9.0-9.5; the water-based silicone resin used is an ionic water-based silicone resin, provided by Shenyang Caiyi Special Coatings Co., Ltd., with a temperature resistance of ≥600°C, a solid content of ≥45%, and a pH value of 6.0-8.0.

[0061] The polycarboxylic acid high-efficiency water-reducing agent used is WSM-M polycarboxylic acid high-efficiency water-reducing agent provided by Hubei Siman New Materials Co., Ltd., and its water reduction rate is ≥35%.

[0062] The self-crosslinking acrylate emulsion used was provided by Kunshan Development Zone Lianle Chemical Trading Co., Ltd., model la-1025, which is anionic, the main synthetic monomers are acrylate and methacrylate, solid content (40%), average particle diameter of 0.2 to 0.4 μm, and pH value of 6.0 to 8.0.

[0063] Example 1

[0064] A self-repairing thermal insulation material for medium and high pressure steam pipelines, the raw material components and weight percentages of which are as follows:

[0065] Modified waste aluminum silicate refractory fibers 26% (9% modified waste aluminum silicate refractory short fibers 3-5mm, 17% modified waste aluminum silicate refractory short fibers 1-1.5mm); self-repairing composite powder 15%; 200-mesh lightweight floating beads 10%; fumed nano-silica 5%; titanium dioxide 3%; potassium hexatitanate whiskers 3%; 300-mesh sintered magnesia powder (MgO content ≥98%) 6%; binder 30% (25% silica sol, 600°C heat-resistant ionic water-based silicone resin 6%); composite water reducer 1.8% (0.3% WSM-M polycarboxylate high-efficiency water reducer, 1.5% sodium tripolyphosphate); citric acid retarder 0.2%;

[0066] Among them, the self-repairing composite powder used has a particle size of 1200 mesh, and the raw materials and their mass percentages are: self-crosslinking acrylic emulsion 27%, high polyammonium phosphate (polymerization degree 1000) 15%, dipentaerythritol 4%, melamine 6%, silicon aluminum oxide thermal insulation filler powder (particle size 1600 mesh) 30%, and deionized water 18%; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, high polyammonium phosphate, dipentaerythritol, melamine, silicon aluminum oxide thermal insulation filler powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain a self-repairing composite powder;

[0067] The silicon aluminum oxide heat-insulating filler powder (particle size of 1600 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers;

[0068] The density of the fumed nano-silica is 0.05 g / cm 3 , specific surface area 600m 2 / g, average particle size is 35nm, SiO2 content is 99.8%;

[0069] The titanium dioxide is rutile, has a particle size of 300 mesh, and a TiO2 content of 94.3%;

[0070] The potassium hexatitanate whiskers have a diameter of 2 to 4 μm and an aspect ratio of 10 to 15;

[0071] The method for preparing the self-repairing thermal insulation material for medium and high pressure steam pipelines comprises the following steps:

[0072] 1) The weighed modified waste aluminum silicate refractory fiber, self-repairing composite powder, lightweight floating beads, fumed nano-silica, titanium dioxide, potassium hexatitanate whiskers, coagulant, composite water reducer and retarder are added to a blender, first adding two-thirds of the amount of 3-5 mm modified aluminum silicate refractory short fibers and the entire amount of 1-1.5 mm modified waste aluminum silicate refractory short fibers and lightweight floating beads, stirring for 5 minutes, then adding the self-repairing composite powder, coagulant and retarder at one time, and gradually adding the remaining amount of 3-5 mm modified waste aluminum silicate refractory short fibers while stirring, and continuing to stir for 10 minutes to obtain a solid mixture, which is packaged in a waterproof sealed package with a shelf life of 6 months;

[0073] 2) Packaging of binder mixture: Weigh silica sol and water-soluble silicone resin according to weight percentage, stir for more than 5 minutes, mix evenly to prepare binder, and package in plastic barrels with a shelf life of 12 months;

[0074] 3) On-site construction of spray coating: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for more than 5 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 120 minutes at an ambient temperature of 30°C.

[0075] Example 2

[0076] A self-repairing thermal insulation material for medium and high pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:

[0077] 1) Modified waste aluminum silicate refractory fibers 26% (6% modified waste aluminum silicate refractory short fibers 3-5 mm, 20% modified waste aluminum silicate refractory short fibers 1-1.5 mm); self-repairing composite powder 12%; 200-mesh lightweight floating beads 8%; fumed nano-silica 5%; titanium dioxide 2%; potassium hexatitanate whiskers 3%; 300-mesh sintered magnesia powder (MgO content ≥98%) 9%; binder 33% (25% silica sol, 8% ionic water-based silicone resin with a temperature resistance of 600°C); composite water reducer 1.9% (0.2% WSM-M polycarboxylic acid high-efficiency water reducer, 1.7% sodium tripolyphosphate); 0.1% citric acid retarder;

[0078] Among them, the self-repairing composite powder used has a particle size of 1200 mesh, and the raw materials and their mass percentages are: self-crosslinking acrylic emulsion 24%, high polyammonium phosphate (polymerization degree 1000) 12%, dipentaerythritol 3%, melamine 6%, silicon aluminum oxide thermal insulation filler powder (particle size 1600 mesh) 35%, and deionized water 20%; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, high polyammonium phosphate, dipentaerythritol, melamine, silicon aluminum oxide thermal insulation filler powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain a self-repairing composite powder;

[0079] The silicon aluminum oxide heat-insulating filler powder (particle size of 1600 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers;

[0080] The density of the fumed nano-silica is 0.05 g / cm 3 , specific surface area 600m 2 / g, average particle size is 35nm, SiO2 content is 99.8%;

[0081] The titanium dioxide is rutile, has a particle size of 300 mesh, and a TiO2 content of 94.3%;

[0082] The potassium hexatitanate whiskers have a diameter of 2 to 4 μm and an aspect ratio of 10 to 15;

[0083] 2) On-site construction of spray coating: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 10 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 150 minutes at an ambient temperature of 10°C.

[0084] Example 3

[0085] A self-repairing thermal insulation material for medium and high pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:

[0086] 1) Modified waste aluminum silicate refractory fibers 32% (12% of 3-5mm modified zirconium-containing waste aluminum silicate refractory short fibers, 20% of 1-1.5mm modified zirconium-containing waste aluminum silicate refractory short fibers); self-repairing composite powder 10%; 80-mesh lightweight floating beads 12%; fumed nano-silica 4%; titanium dioxide 3%; potassium hexatitanate whiskers 3%; 300-mesh sintered magnesia powder (MgO content ≥98%) 7%; binder 26% (18% of silica sol, 8% of 600°C heat-resistant ionic water-based organic silicone resin); composite water reducer 3.4% (0.3% of WSM-M polycarboxylic acid high-efficiency water reducer, 3.1% of sodium tripolyphosphate); citric acid retarder 0.1%;

[0087] Among them, the self-repairing composite powder used has a particle size of 1200 mesh, and the raw materials and their mass percentages are: self-crosslinking acrylic emulsion 20%, high polyammonium phosphate (polymerization degree 1200) 15%, dipentaerythritol 6%, melamine 8%, silicon aluminum oxide thermal insulation filler powder (particle size 1600 mesh) 23%, and deionized water 28%; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, high polyammonium phosphate, dipentaerythritol, melamine, silicon aluminum oxide thermal insulation filler powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain a self-repairing composite powder;

[0088] The silicon aluminum oxide heat insulating filler powder (particle size of 1600 mesh) is obtained by high-energy ball milling of 1-1.5 mm zirconium-containing waste aluminum silicate refractory short fibers;

[0089] The density of the fumed nano-silica is 0.048 g / cm 3 , specific surface area 650m 2 / g, average particle size is 15nm, SiO2 content is 99.9%;

[0090] The titanium dioxide is rutile, has a particle size of 400 mesh, and a TiO2 content of 95.6%;

[0091] The potassium hexatitanate whiskers have a diameter of 2 to 4 μm and an aspect ratio of 15 to 20;

[0092] 2) On-site construction of spray coating: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for more than 10 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 180 minutes at an ambient temperature of 10°C.

[0093] Example 4

[0094] A self-repairing thermal insulation material for medium and high pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:

[0095] 1) Modified waste aluminum silicate refractory fibers 26% (3-5mm modified zirconium-containing waste aluminum silicate refractory short fibers 12%, 1-1.5mm modified zirconium-containing waste aluminum silicate refractory short fibers 14%); self-repairing composite powder 15%; 80-mesh lightweight floating beads 12%; fumed nano-silica 3%; titanium dioxide 3%; potassium hexatitanate whiskers 2%; 300-mesh sintered magnesia powder (MgO content ≥98%) 6%; binder 30% (24% silica sol, 600°C heat-resistant ionic water-based organic silicone resin 6%); composite water reducer 2.85% (0.25% WSM-M polycarboxylate high-efficiency water reducer, 2.6% sodium tripolyphosphate); 0.15% citric acid retarder;

[0096] Among them, the self-repairing composite powder used has a particle size of 1300 mesh, and the raw materials and their mass percentages are: 35% self-crosslinking acrylic emulsion, 10% high polyammonium phosphate (polymerization degree 1200), 5% dipentaerythritol, 8% melamine, 24% silicon aluminum oxide thermal insulation filler powder (particle size ≤1600 mesh), and 18% deionized water; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, high polyammonium phosphate, dipentaerythritol, melamine, silicon aluminum oxide thermal insulation filler powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain a self-repairing composite powder;

[0097] The silicon aluminum oxide heat-insulating filler powder (particle size of 1700 mesh) is obtained by high-energy ball milling of 1-1.5 mm zirconium-containing waste aluminum silicate refractory short fibers;

[0098] The density of the fumed nano-silica is 0.048 g / cm 3 , specific surface area 650m 2 / g, average particle size is 15nm, SiO2 content is 99.9%;

[0099] The titanium dioxide is rutile, has a particle size of 400 mesh, and a TiO2 content of 95.6%;

[0100] The potassium hexatitanate whiskers have a diameter of 2 to 4 μm and an aspect ratio of 15 to 20;

[0101] 2) On-site construction of spray coating: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 10 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 120 minutes at an ambient temperature of 30°C.

[0102] Example 5

[0103] A self-repairing thermal insulation material for medium and high pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:

[0104] 1) Modified waste aluminum silicate refractory fibers 29% (3-5mm modified waste aluminum silicate refractory short fibers 10%, 1-1.5mm modified waste aluminum silicate refractory short fibers 19%); self-repairing composite powder 14%; 140-mesh lightweight floating beads 11%; fumed nano-silica 5%; titanium dioxide 3%; potassium hexatitanate whiskers 2.1%; 400-mesh sintered magnesia powder (MgO content ≥98%) 8%; binder 26% (21% silica sol, 600°C heat-resistant ionic water-based organic silicone resin 5%); composite water reducer 1.7% (0.4% WSM-M polycarboxylic acid high-efficiency water reducer, 1.3% sodium tripolyphosphate); 0.2% citric acid retarder;

[0105] Among them, the self-repairing composite powder used has a particle size of 1300 mesh, and the raw materials and their mass percentages are: 30% self-crosslinking acrylic emulsion, 15% high polyphosphate ammonium (polymerization degree 1000), 3% dipentaerythritol, 4% melamine, 20% silicon aluminum oxide thermal insulation filler powder (particle size ≤1600 mesh), and 28% deionized water; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, high polyphosphate ammonium, dipentaerythritol, melamine, silicon aluminum oxide thermal insulation filler powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain a self-repairing composite powder;

[0106] The silicon aluminum oxide heat-insulating filler powder (particle size of 1700 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers;

[0107] The density of the fumed nano-silica is 0.05 g / cm 3 , specific surface area 600m 2 / g, average particle size is 35nm, SiO2 content is 99.8%;

[0108] The titanium dioxide is rutile, has a particle size of 300 mesh, and a TiO2 content of 94.3%;

[0109] The potassium hexatitanate whiskers have a diameter of 2 to 4 μm and an aspect ratio of 10 to 15;

[0110] 2) On-site construction of spray coating: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 5 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 120 minutes at an ambient temperature of 35°C.

[0111] Comparative Example 1

[0112] The medium-pressure steam pipeline of a steel plant (steam pressure 3.82MPa, temperature 400℃, pipe diameter 273mm) is wrapped with a double-layer aluminum silicate wool needle-punched blanket with a total thickness of 60mm and a bulk density of 128kg / m 3 , maximum operating temperature 1000℃, thermal conductivity 0.087W / m·K (hot surface temperature 300℃).

[0113] Standard samples were prepared according to the self-repairing insulation materials for medium and high pressure steam pipelines of Examples 1 to 5, cured under natural conditions, demolded after 12 hours, and heat treated at 400°C for 3 hours before testing of bulk density, compressive strength, and thermal conductivity. The specific data are shown in Table 1. It can be seen that the bulk density of each sample is between 0.39 and 0.51 g / cm 3 The compressive strength is between 0.92 and 1.35 MPa, and the thermal conductivity (hot surface temperature 300°C) is between 0.055 and 0.078 W / m·K. The scanning electron microscope photos and XRD diffraction patterns of the self-repairing insulation material for medium and high pressure steam pipelines in Example 1 after heat treatment at 400°C for 3 hours are as follows: Figures 1-2 shown.

[0114] Furthermore, according to Examples 1 to 5, self-repairing insulation materials for medium and high pressure steam pipes were prepared and tested in a medium-pressure steam pipe of a steel plant (steam pressure 3.82 MPa, temperature 400°C, pipe diameter 273 mm, insulation layer thickness 60 mm). Compared with the original multi-layer aluminum silicate needle-punched blanket insulation layer, it has the advantages of good insulation structure integrity, high heat barrier and heat reflection performance, crack self-repair, green environmental protection and good waterproofness.

[0115] Table 1. Comparison of performance indicators and application effects between the embodiments of the present invention and the comparative examples

[0116]

[0117]

[0118] Comparative Example 2

[0119] A self-repairing thermal insulation spray coating, prepared by a method substantially similar to that of Example 1, differs in that, in the preparation method of modified waste aluminum silicate refractory fibers, conventional mechanical vibrating screens are used for vibratory screening, rather than ultrasonic vibrating screens. After heat treatment at 400°C for 3 hours, the resulting standard sample exhibited a thermal conductivity of 0.095 (W / m·K) at a hot surface temperature of 300°C, exceeding that of Example 1. Furthermore, in a field industrial test, the average outer surface temperature of the pipe after one year of use was 35°C, also exceeding that of Example 1.

[0120] Comparative Example 3

[0121] A self-repairing thermal insulation spray coating was prepared using a method similar to that used in Example 1, except that the self-crosslinking acrylic emulsion was replaced with a water-based acrylic emulsion produced by Qingdao Enze Chemical Co., Ltd. Because the self-crosslinking acrylate emulsion does not self-crosslink, a crosslinking agent was added during the preparation of the self-repairing composite powder. After mixing, the mixture was heated to 150°C and held for 60 minutes. After heat treatment at 400°C for 3 hours, the resulting standard sample exhibited a thermal conductivity of 0.113 W / m·K at a hot surface temperature of 300°C, exceeding that of Example 1.

[0122] Comparative Example 4

[0123] A self-repairing thermal insulation spray coating, the preparation method of which is roughly the same as that of Example 1, except that the mass percentages of the raw materials in the self-repairing composite powder used are as follows: 27% self-crosslinking acrylic emulsion, 15% high polyammonium phosphate (polymerization degree 1000), 4% dipentaerythritol, 36% silicon aluminum oxide thermal insulation filler powder (particle size 1600 mesh), and 18% deionized water.

[0124] Using the above-mentioned self-healing composite powder formulation system, the self-cross-linking reaction of the self-cross-linking acrylic emulsion is not sufficient within the same reaction time, and the composition of the prepared self-healing composite powder is uneven; the thermal conductivity of the prepared standard sample is 0.105 (W / m·K) at the hot surface temperature of 300°C, which is greater than the thermal conductivity coefficient of Example 1.

[0125] Comparative Example 5

[0126] A self-repairing thermal insulation spray coating, the preparation method of which is roughly the same as that of Example 1, except that the weight percentages of the self-repairing composite powder, 3-5mm modified waste aluminum silicate refractory short fibers and 1-1.5mm modified waste aluminum silicate refractory short fibers are 8%, 28% and 5% respectively.

[0127] The thermal conductivity of the prepared standard sample was 0.085 (W / m·K) at a hot surface temperature of 300°C, which was slightly higher than the thermal conductivity of Example 1. In addition, the self-repairing composite powder content and the short fiber gradation did not reach a reasonable range. After one year of use in the on-site industrial test, the average outer surface temperature of the pipeline was 37°C, resulting in an online crack thermal repair effect that was inferior to that of Example 1.

[0128] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art who, within the technical scope disclosed by the present invention, makes equivalent substitutions or changes based on the technical solutions and improved concepts of the present invention shall be covered by the scope of protection of the present invention.

Claims

1. A self-repairing thermal insulation material for medium and high pressure steam pipelines, characterized in that: The invention comprises the following raw materials in weight percentage: 10-15% of self-repairing composite powder, 3-5% of fumed nano-silica, 2-3% of titanium dioxide, 2-3% of potassium hexatitanate whiskers, 20-32% of modified waste aluminum silicate refractory short fibers, 8-12% of lightweight floating beads, 6-9% of accelerator, 23-33% of binder, 1.5-3.5% of composite water reducer, and 0.1-0.2% of retarder; the modified waste aluminum silicate refractory fibers are obtained by vibrating and screening the waste aluminum silicate refractory fibers and performing surface modification with polyethylene glycol solution, and the fibers have two sizes of 1-1.5 mm and 3-5 mm; the raw materials of the self-repairing composite powder comprise self-cross-linking acrylic emulsion, high polyammonium phosphate, dipentaerythritol, melamine, silicon aluminum oxide thermal insulation filler powder and water.

2. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 1, characterized in that: The raw materials and their mass percentages include: 20-35% of self-crosslinking acrylic emulsion, 10-15% of high polyammonium phosphate, 3-6% of dipentaerythritol, 4-8% of melamine, 20-35% of silicon aluminum oxide heat insulation filler powder and 18-28% of water.

3. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 2, characterized in that: The self-crosslinking acrylic ester emulsion is anionic, the main synthetic monomers are acrylic ester and methacrylic ester, the solid content is ≥40%, the average particle diameter is 0.2-0.4um, and the pH value is 6.0-8.0; the polymerization degree of the high polyammonium phosphate is ≥1000.

4. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 1, characterized in that: The vibration screening step includes: shearing the waste aluminum silicate refractory fibers into short fibers of 3 to 5 mm, and then screening them using a vibration screen with a pore size of 3 mm to obtain waste aluminum silicate refractory short fibers of 3 to 5 mm; then taking part of the obtained 3 to 5 mm waste aluminum silicate refractory short fibers and further shearing them into short fibers of 1 to 1.5 mm, and screening them using a vibration screen with a pore size of 1 mm to obtain waste aluminum silicate refractory short fibers of 1 to 1.5 mm.

5. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 1, characterized in that: The surface modification step comprises: spraying a polyethylene glycol solution on the waste aluminum silicate refractory short fibers.

6. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 1, characterized in that: The density of the fumed nano-silicon dioxide is ≤0.05 g / cm 3 , specific surface area ≥600m 2 / g, particle size is 7-40nm, SiO2 content ≥99.8%; titanium dioxide is rutile type, particle size ≤300 mesh, TiO2 content ≥94wt%.

7. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 1, characterized in that: The potassium hexatitanate whisker has a diameter of 2-4 μm and an aspect ratio of 10-20.

8. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 1, characterized in that: The binder includes silica sol and water-based silicone resin.

9. The self-repairing thermal insulation material for medium and high pressure steam pipelines according to claim 1, characterized in that: The composite water reducing agent comprises a polycarboxylate high-efficiency water reducing agent and sodium tripolyphosphate.

10. The method for preparing the self-repairing thermal insulation material for medium and high pressure steam pipelines according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh the modified waste aluminum silicate refractory short fibers, self-repairing composite powder, lightweight floating beads, fumed nano-silica, titanium dioxide, potassium hexatitanate whiskers, accelerators, binders, composite water reducers and retarders according to the proportion, first add part of the modified waste aluminum silicate refractory short fibers and the entire amount of lightweight floating beads into a blender, stir, then add the weighed self-repairing composite powder, fumed nano-silica, titanium dioxide, potassium hexatitanate whiskers, accelerators and retarders, add the remaining amount of modified waste aluminum silicate refractory short fibers under stirring, stir to obtain a solid mixture; 2) The solid mixed material and the binder are mixed and stirred evenly to obtain the self-repairing thermal insulation material for medium and high pressure steam pipelines.

Citation Information

Patent Citations

  • High-pressure steam pipeline heat preservation structure and construction method

    CN114738548A